The Journal of Education and Humanities, Vol. 4, 2021 - McPherson, Akima; Goolsarran, Mohandatt; Rose, Pamela; Kendall, Andrew; Khan, Michael (Faculty of Education and Humanities, University of Guyana, 2021)
This fourth issue of the Journal of Education and Humanities (JEH) continues to fulfill its commitment to lecturers in the Faculty of Education and Humanities, University of Guyana, to assist them in developing their research profiles and output in a refereed journal, and to provide findings from invaluable critical literary analyses and research studies in Education. These peer-reviewed articles inform future improvements in key subject areas of Education and expand the body of critical literary works. In addition, it extends the same opportunity to lecturers in another area of academic study offered by the Faculty: the Fine Arts. These findings analyses and recommendations could stimulate further research in Guyana, the Caribbean, and internationally. Such findings and analyses are included in two research papers on English and Mathematics, the two compulsory subjects in our regional Caribbean Secondary Examination Certificate (CSEC), two analyses of literary works, as well as the statement and display of works of Michael Khan, one of the long-serving lecturers in the Creative Arts Division who won the first prize in the Fine Craft category for one of his pieces at the 2017 Guyana Visual Arts Competition and Exhibition. Khan shares a statement of himself as an artist, allowing us the opportunity to view samples of his work from his perspectives and in support of his claim that his creative compositions capture and manipulate simple art forms as he conveys his ideas. An outstanding feature of this issue is the attention paid to Mathematics and English by two active researchers in Education. Mohandatt Goolsarran focuses attention on all the stakeholders involved in the teaching of Mathematics in secondary schools in Guyana. His paper provides well-examined data to suggest future decisions at the regional, national and school levels while highlighting the need to synchronise changing curricula demands with technology. Pamela Rose addresses the gender disparity that affects male and female students’ preferences for writing instructions in classrooms in a Creole-speaking context, an area in which research is sparse. Her findings not only point to the need to equip secondary school English teachers with the knowledge and skills needed to create meaningful metalinguistic tasks to distinguish Creole and Standard English codes, but also to change the existing monolingual language policy and the development of learners’ self-efficacy in writing. Another outstanding and unique feature of this issue is a comparative approach to analysis in the next two papers. As a discipline, comparative literature emerged in the early nineties, but these two papers have the distinction of applying the methodology to different genres – fine arts and literature, and literature and film. On the one hand, Akima McPherson juxtaposes the imprinting of a sexualized and racialized denigration of the black female body (portrayed as a modified Classical Greek/Western nude while bearing undertones of West-African aesthetics), in an earlier painting and an ode, with the more recent Caribbean sculpture of the liberated and proud black female body (a national monument in Jamaica), imbued with clear and defined attributes of West African figuration, a juxtaposition that leads to the acceptable conclusion that this latter work embodies freedom from the shackles of white patriarchy. On the other hand, Andrew Kendall takes us on a well-informed international ‘journey’ in the comparison of a West German novella and film, written and produced in the 1970s. Both focus on the Cold War. In this paper, a careful and intriguing critique is made of how the writers of both genres responded to the paranoia caused in society by the Cold War, as well as how they portrayed the uncertainty of truth and meaning in the social climate during that era in their use of language. As readers, we are left to decide whether we agree with the writer’s claim that the dual value of these contemporaneous explorations are key factors in presenting such concerns.
Keywords: education; humanities; journals